Effects of COVID-19 Pandemic on Investor Attention in Global Stock Markets: An Empirical Assessment. Issue 2 (March 2023) - Goel, Garima; Dash, Saumya Ranjan; Debata, Byomakesh
Using the data from 50 global stock markets, this article examines the impact of the COVID-19 pandemic on investor attention. Using Google search volume as a proxy for country-specific and worldwide investor attention, this article provides initial evidence on the relationship between the spread of the pandemic and investor attention. Our results suggest that the increasing number of daily deaths and confirmed cases significantly negatively impact investor attention. Results are robust to the country characteristics like the nature of the financial system, financial stability and investor attention risk pricing nature. Our results indicate a positive and significant impact of government responses for restoring investor attention in the market. JEL Codes: G10, G14, G15, C23